EXPLORING ENGLISH FOREIGN LANGUAGE ANXIETY AND ACADEMIC MOTIVATION: A QUALITATIVE CASE STUDY OF UNDERGRADUATE STUDENTS’ PERSPECTIVES AND EXPERIENCES IN KAZAKHSTAN - Kenzhetayeva, Aigul (Nazarbayev University Graduate School of Education, 2024)
There is an increasing amount of research conducted on foreign language anxiety (FLA), yet the studies conducted in the Kazakhstani context are still very few (Duysembekova & Kurban, 2022; Myrzakulova, 2019; Plyushko, 2018). The purpose of this study was to explore the factors influencing FLA and academic motivation. By exploring the factors contributing to FLA, the qualitative study seeks to uncover the root causes and triggers of this anxiety in one English medium instruction (EMI) university in Kazakhstan. The study also aimed to understand the nuances influencing English as a foreign language (EFL) students’ learning journey and academic motivation in EMI context. The findings reported that social and psychological factors impacted students’ FLA and academic motivation. This including socio-environmental factors such as pedagogical, teacher- student relationship, and peer impact. Understanding the underlying causes of FLA concerning academic motivation in EFL undergraduate students is crucial for educators, educational institutions, and policymakers to develop targeted strategies and support systems that can enhance a positive learning experience.
Keywords: Type of access: Embargo; foreign language anxiety; EFL (English as foreign language); academic motivation